A Simple, Effective Technique for Port-Site Closure After Laparoscopy - Botea, Florin (Society of Laparoendoscopic Surgeons, 2011)
BACKGROUND AND OBJECTIVES: Fascial closure of port sites represents a challenging issue in laparoscopic surgery. The aim of this article is to introduce a procedure that allows the safe suturing of the abdominal fascia in these wounds. METHODS: We herein describe a simple technique for fascial closure after laparoscopy using a transcutaneous approach and standard surgical instruments for suture. RESULTS: The method was used in 34 patients with no intraoperative incidents and no port-site hernias during a mean follow-up of 23.9 months (median 20.5, range 5 to 47). CONCLUSION: The procedure is easy to perform, safe, fast, and inexpensive.